Efektivitas Aplikasi Marbel Berbasis Android untuk Meningkatkan Kemampuan Membaca Permulaan pada Anak Disleksia: Single Subject Research di SDN 28 Batipuh, Kabupaten Tanah Datar - Fitriani, Aura Syfa; Susanti, Roza Eva (YASIN, 2025)
Difficulties in beginning reading skills in second-grade students, especially those who show characteristics of dyslexia, are still a challenge in basic education. This study aims to evaluate the effectiveness of using Marbel application in improving beginning reading skills in dyslexic children. The approach used was a quantitative method with Single Subject Research (SSR) A-B-A experimental design. Data were obtained through a reading test adapted from an instrument developed by Sonia Triandani Yolanda and Damri (2022), with a reliability coefficient of 0.979. The research subjects were second-grade students of SDN 28 Batipuh. The results of the visual analysis of graph data show that in the initial baseline phase (A1), the subject has a stable reading ability level of 13% for five observations. In the intervention phase (B) which lasted for six observations, there was an increase in reading ability, with a stable achievement at 87%. Furthermore, in the final baseline phase (A2), after four observations, reading ability further increased to reach 92%. The findings show that Marbel app is an effective learning media in improving beginning reading skills for children with dyslexia at the primary school level.